Tindak Tutur Lokusi dalam Film Cinta Laki-Laki Biasa Karya Asma Nadia - Sani Okda Manesa; Irwan Siagian (Journal on Education, 2023)
The purpose of this research is to find out the form of locutionary speech acts of locutionary in the film "Ordinary Male Love" (2016)". The researcher used a qualitative descriptive research type in this study. The dialogues of the characters in the film "Ordinary Male Love" (2016)" as a data source in this research. The film used in this study is the film Cinta Men Ordinary which is closely related to the culture and habits of society in Indonesia. In collecting data, the researchers used the technique of free-involved viewing and notes in this study as instruments in this study, then validated by expert judgment or other lecturers. The method used to analyze or as an analytical knife in this study uses pragmatic methods. Based on the results of data analysis found by researchers, it can be concluded into two. First, the forms of locutionary speech acts found in the film Cinta Men Ordinary are declarative, imperative, and interrogative